Pengukuran Kinerja Dengan Menggunakan Empat Persfektif dari Balance Score Card Pada PT Pengembangan Pariwisata Indonesia ( PERSERO) Nusa Dua Bali - Ni Putu Medyani; I Made Sudana; A.A. Putri Suardani; Istiarto Istiarto (Fakultas Ekonomi Universitas Islam Al-Azhar, 2019)
This purpose of this study to determine the performance of Indoneia Tourism Development Corporation Nusa Dua Bali is measured by using for perspectives from Balanced Scorecard, that is financialperspective, customer perspective, internal business process perspective, and learning & growth perspective. Data used in this research are primary data and secondary data. Performance measurement of financial perspective is measured using current ratio, quick ratio, debt to equity ratio, debt to aset ratio, return on investment, and return on equity. Performance measurement of internal business process perspecive is seen from the level of innovattion, and after sales services in terms of handling customer complaints. Performance measurement of learning and growth perspective is measured using employee satisfaction level, employee retentio, and employee productivity. Based on the analysis that has been done, the performance measurement of the customer perspective is good, the performance measurement of the overall customer persfective is good, the performance measurement of the overall internal business process perspective is good, and the performance measurement of the overall learning and growth perspective is good.